Effectiveness of Fining Agents for Wax Apple (Syzygium samarangense) Wine Clarification - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2019)
Waxe apple fruits are rich sources of nutrition with water, carbohydrate, protein, vitamins, and minerals, along with some medicinal properties. This fruit is highly perishable because of its thin skin and can be easily damaged. The processing of wax apple juice into wine could enhance the value of the fruit. However, turbidity in waxe apple wine is a major problem limiting its contribution to international commercialization. Wine clarification is a widely applicable procedure that involves an agent or a mixture being supplemented to clarify, stabilize or modify the sensory wine attributes. Objective of this study focused on the feasibility of different fining agents such as gluten, gelatin, maize zein, casein, bentonite for clarification of waxe apple wine. This research also examined if there was any synergistic effect while combining gluten with gelatin to improve their fining capability. Our results revealed that 5.0:3.0 g/hL (gluten: gelatin) was adequate to control the haze cloud or turbidity after 3rd week racking of waxe apple wine.Keywords: Waxe apple, Wine, Fining, Clarification, Turbidity, Gluten, Gelatin.